The Problem of Hate Speech: Beliefs of Chilean Students About Hate Speech with an Emphasis on Gender Perspectives - Jesús Marolla-Gajardo; María del Consuelo Díez-Bedmar (Social Sciences)
This study examines hate speech with a gender perspective in the educational field, focusing on the beliefs of Chilean History degree students regarding its prevalence in their academic programs. Using a quantitative methodology with a representative sample (n = 998) and robust statistical reliability (99% confidence, and 4% margin of error), the research highlights the intersection of hate speech and teacher training. The findings reveal an urgent need for reforms in teacher training curricula to address hate speech effectively. Participants report insufficient tools to confront these challenges, both during their studies and in their future professional practice, exposing a critical gap in preparing educators to promote inclusive learning environments. The study emphasizes incorporating social justice and human rights education as fundamental components of teacher training, advocating for their integration into curricula to foster equity and respect for diversity. By addressing the complexities of hate speech within educational contexts, this research provides practical implications for policy reform and program development. These findings contribute significantly to the literature, offering actionable insights for combating hate speech and advancing gender-sensitive education while establishing a foundation for future research and practical interventions.